Integrating Gender into Transport Planning From One to Many Tracks - Scholten, Christina Lindkvist; Joelsson, Tanja (Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This edited collection brings together feminist research on transport and planning from different epistemologies, with the intention to contribute to a more holistic transport planning practice. With a feminist perspective on transport policy and planning, the volume insists on the political character of transport planning and policy, and challenges gender-blindness in a policy area that impacts the everyday lives of women, men, girls, and boys. The chapters discuss everyday mobility as an embodied and situated activity in both conceptual and theoretical ways and suggest practical tools for change. The contributions of this collection are threefold: integrating gender research and transport planning, combining quantitative and qualitative gender research perspectives and methods, and highlighting the need to acknowledge the politicization of transport planning and transport practice.